DESCRIPTION FACTORS (PREDISPOSING, ENABLING AND SUPPORTING) IN MOTHER WHO MAKE POSTPARTUM VISITS - Ayumi Kulsum Maulida; Reni Wahyu Triningsih; Desy Dwi Cahyani (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2023)
Postpartum visits are carried out to monitor the health of the postpartum mother,detect early and prevent complications during the postpartum period which arecarried out at least 4 times. The target for postpartum visits in Malang Regency in2021 is still lacking, namely 88.32%. The purpose of this study was to describe thecharacteristics of postpartum mothers making postpartum visits at the clinic. Theresearch design is a quantitative descriptive. The research sample for postpartummothers was 38 people. the sample was selected by using purposive samplingtechnique. The research instrument is a questionnaire. The predisposing factorsstudied were knowledge and attitudes. The enabling factors studied were costs,access to transportation and distance; The reinforcing factor studied was familysupport.The results showed that 68% of postpartum mothers made 2 postpartum visits.Predisposing factors: 42% of postpartum mothers have sufficient knowledge and58% of postpartum mothers have a positive attitude towards postpartum visits. In theenabling factor variables, it was found that 100% of postpartum mothers usedpersonal costs for postpartum visits, 100% of postpartum mothers had easytransportation access and 74% of postpartum mothers were home to the clinic >3KM away. Supporting factors are known to be 61% of families of postpartum motherswho support mothers to make postpartum visits. Health workers need to increaseknowledge variables, encourage a more positive attitude of mothers and advocate forfamilies to support postpartum mothers in conducting postpartum visits